MEMPREDIKSI KECENDERUNGAN PERUSAHAAN MELAKUKAN PENGHINDARAN PAJAK - Yudhanta Sambharakreshna; Nurul Kompyurini (InFestasi, 2016)
This study aimed to analyze and predict the executive character, profitability, and corporate governance to tendency ofcompany doing tax avoidance. Samples are 45 companies joined in 45 LQ Indonesia Stock Exchange during 2009 until2013. Samples were selected using purposive sampling method. Data was analyzed using descriptive analysis method,multiple linear regression, hypothesis testing. The results of this study indicate that the character of executives andprofitability affect to the tax avoidance, while the audit committee and independent commissioner has no effection to the taxavoidance.